Prospective study to find out the role of cerebrospinal fluid examination by cartridge-based nucleic acid amplification test and culture and sensitivity as a diagnostic method in childhood central nervous system tuberculosis - Solanki, Daya Lal; Jain, Anil Kumar; Garg, Pukhraj; Karnawat, Bhag Singh; Narayan, Jaiprakash (Indian Journal of Child Health, 2019)
Introduction: Central nervous system (CNS) tuberculosis (TB), particularly tuberculous meningitis, is the severest form of Mycobacterium tuberculosis (MTB) infection causing severe neurological defects or even death. The recent introduction of cartridge-based nucleic acid amplification test (CBNAAT) has significantly transformed the diagnostics of TB in adults, but its application for the diagnosis of pediatric TB is under evaluation. Objective: This study was conducted by for cerebrospinal fluid (CSF) examination in the detection of MTB by the culture and sensitivity and CBNAAT in the diagnosis of childhood CNS TB. Methods: A prospective hospital-based study was conducted from July 2017 to June 2018 in the pediatric department of a tertiary care unit. A total of 65 randomly selected patients, suspected of CNS TB, were included in this study. CSF was tested for CBNAAT and culture and sensitivity other routine investigations such as specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated for both CBNAAT and culture and sensitivity. Mantoux test was also performed, and the statistical analysis was performed using Chi-square test. p=0.05 was considered to be statistically significant. Results: Culture positive TB was found in 26 out of the 65 children. The sensitivity, specificity, PPV, and NPV for CBNAAT and culture and sensitivity were 65.71%, 90.00%, 88.46%, and 69.23%, respectively. CBNAAT was detected to be more in 12 TB cases and was more sensitive than culture and sensitivity. Positive history of contact (p=0.04), reactive Mantoux test (p<0.005), presence of Bacillus Calmette Guerin (BCG) scar (p=0.02), and low socioeconomic status were independently associated with a positive CBNAAT result. Conclusion: Analysis of CSF sample with CBNAAT is a sensitive and specific method for rapid diagnosis of CNS TB in children. Compared to culture and sensitivity, CBNAAT offers better sensitivity and its scale-up will improve access to CNS TB diagnostics in children. Although a negative CBNAAT does not rule out TB.